2009
DOI: 10.1063/1.3054180
|View full text |Cite
|
Sign up to set email alerts
|

Separate charge transport pathways determined by the time of flight method in bimodal polytriarylamine

Abstract: Time of flight photocurrent transient studies on thin films of bimodal polytriarylamine (PTAA) show two distinct and separate arrival times for hole transport in the same sample at a single field. The corresponding mobilities differ by two orders of magnitude, typically μfast∼10−3 cm2 V−1 s−1 and μslow∼10−5 cm2 V−1 s−1 at room temperature, and are measured parametric in electric field and temperature. The mobility data are analyzed using the correlated disorder model by Novikov, yielding a fitting parameter se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 11 publications
6
30
0
Order By: Relevance
“…the area under the transient curves) with an increase in the applied voltage. This observation is attributed to the field dependence of the carrier drift length, as has been found elsewhere [7,22]. The transient photocurrents in our devices exhibit some dispersive behaviour, which is commonly observed in polymer-based systems [7,8,[22][23][24].…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…the area under the transient curves) with an increase in the applied voltage. This observation is attributed to the field dependence of the carrier drift length, as has been found elsewhere [7,22]. The transient photocurrents in our devices exhibit some dispersive behaviour, which is commonly observed in polymer-based systems [7,8,[22][23][24].…”
Section: Resultssupporting
confidence: 53%
“…This observation is attributed to the field dependence of the carrier drift length, as has been found elsewhere [7,22]. The transient photocurrents in our devices exhibit some dispersive behaviour, which is commonly observed in polymer-based systems [7,8,[22][23][24]. An effective lifetime (τ) was found on a double logarithmic plot as the intersection of asymptotes to the plateau and the linear region of transient's trailing edge [25,26], as is shown in the inset of Figure 2A.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…PTAA polymers have been shown to have high charge carrier mobilities ͑especially when the molecular weight is low͒ 10 and are operationally and environmentally very stable due to a high ionization potential. 11 Indeed, organic field effect transistors produced with PTAA as the semiconducting material and with a hole mobility of 10 −3 cm 2 V −1 s −1 have been used in ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This particular relation has been widely used for a description of transport properties of various materials, we mention here just some recent references. [12][13][14][15][16][17][18] In some papers a comparative analysis of the data using both the GDM and DG model was carried out and it was found that the DG model provides more coherent description of charge transport. 12,16,17 Still, a proper experimental test of the DG model is far from completed.…”
Section: -11mentioning
confidence: 99%